PENGELOLAAN DAYA TARIK PADA FASILITAS OBJEK WISATA AIR PANAS HAPANASAN KABUPATEN ROKAN HULU - Shalsabilla Syahputri; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT Rokan Hulu Regency has the potential to influence (PAD) sources of regional original income. One of them is Hapanasan Hot Spring which is a leading tour which is busy with tourists. Hapanasan Hot Spring has its own charm and its location is close to several other tours. In this study the authors used qualitative methods. the existing facilities at the Hapansan Kab. Rokan Hulu greatly supports the attractiveness of visitors. The uniqueness that is there is more value from visitors and is a differentiator from other objects. Therefore, it is necessary to pay more attention from the Tourism Office and managers to improve existing facilities at the object. The lack of facilities will also hinder the activities of visitors visiting Hapanasan. The attractiveness of tourist objects, starting from their uniqueness, and their beauty and value in the form of various parts of nature, culture, artifacts and so on which are the objects or purposes of visitor visits. In terms of safety, amenities and beach cleanliness, the Hapanasan Hot Springs tourist attraction provides sufficient comfort and facilities for visitors. The existence of tourism support services at tourist destinations is very beneficial for visitors to the Hapanasan Hot Springs. Key : Tourist attractiveness, Hapanasan Hot Springs.